Back Iron Reduction of Single Sided Linear Induction Motor - F.Bonneya, Mehdi (International Journal of Engineering and Technology, 2018)
Finite element analysis is introduced in this work making use of penalty functions for obtaining optimum geometry of Linear Induction Motor (LIM) such as air gap dimension, rotor plate thickness, rotor iron back iron, where optimum values are computed depending on first order penalty function. This technique illustrates the advantage of using numerical analysis where most of linear induction motor optimization previews researches are performed using analytical solution which deal with optimizing of power factor, efficiency, losses, thrust and the geometry does not take into consideration. The best computed values are defined depending on tolerance values where an iterative numerical solution is performed to achieve the excellent values of motor model geometry dimensions.Â